SANDSTONE RESERVOIR DISTRIBUTION ANALYSIS USING SEISMIC INVERSION AND ATTRIBUTES ON âTPBâ FIELD, SOUTH SUMATRA BASIN - Amadea Tampubolon, Devina
Indonesia's significance in the global energy landscape is underscored by its vast reserves of oil and natural gas, which are crucial for both domestic consumption and international markets. To bridge the gap between production and consumption, exploration efforts must be intensified, especially in hydrocarbon-rich regions like the South Sumatra Basin. This study focuses on the "TPB" field within the Jambi Sub-Basin, employing advanced seismic analysis techniques to enhance reservoir characterization and depositional environment interpretation. By integrating AI inversion and seismic attribute analysis, this research aims to delineate sandstone reservoir zones within the Air Benakat Formation (ABF) of the "TPB" field and interpret its depositional environment facies. Acoustic impedance inversion revealed low values indicative of sandstone reservoirs, oriented southeast to northwest, suggesting a tide-dominated estuary facies with sand bar subenvironment. Spectral decomposition outlines the distribution of sandstone reservoir with southeast-northwest trend, representing tide-dominated estuary sandbar, and RMS amplitude shows a similar sandstone reservoirs distribution as observed in the AI and spectral decomposition analysis Sweetness attribute emphasize the sweet spots location in the eastern region of the field which is indicative of potential hydrocarbon reservoir. The comprehensive characterization of the "TPB" field contributes to Indonesia's energy sustainability goals, optimizing exploration and production strategies. By leveraging advanced seismic analysis techniques, this study provides valuable insights into reservoir distribution and depositional environments, essential for informed decision-making in oil and gas exploration and production. As Indonesia pursues its energy independence objectives, a nuanced understanding of reservoir properties facilitated by innovative methodologies will be pivotal in shaping the nation's energy landscape and economic trajectory.